2020
DOI: 10.5324/eip.v14i1.3316
|View full text |Cite
|
Sign up to set email alerts
|

Mandatory childhood vaccination: Should Norway follow?

Abstract: Systematic public vaccination constitutes a tremendous health success, perhaps the greatest achievement of biomedicine so far. There is, however, room for improvement. Each year, 1.5 million deaths could be avoided with enhanced immunisation coverage. In recent years, many countries have introduced mandatory childhood vaccination programmes in an attempt to avoid deaths. In Norway, however, the vaccination programme has remained voluntary. Our childhood immunisation programme covers protection for twelve infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…All in all, researchers disagree at least partly about whether such outcomes, and if so, then more specifically which outcomes, are ethically defensible [22,23,24]. It is not self-evident that mandatory vaccination is the way forward from an ethical perspective, even if one recognises that, in general, the aim is to protect a social good like public health and the individual right to health, and that states have certain responsibilities in this respect [11,25,26].…”
Section: Background Of the Studymentioning
confidence: 99%
See 3 more Smart Citations
“…All in all, researchers disagree at least partly about whether such outcomes, and if so, then more specifically which outcomes, are ethically defensible [22,23,24]. It is not self-evident that mandatory vaccination is the way forward from an ethical perspective, even if one recognises that, in general, the aim is to protect a social good like public health and the individual right to health, and that states have certain responsibilities in this respect [11,25,26].…”
Section: Background Of the Studymentioning
confidence: 99%
“…In another Nordic context, Gamlund et al (2020) [24] point to a recent Norwegian survey experiment by Arnesen et al (2018) [44] on positions on herd immunity, the results of which ''suggested that a concern for others highly influences people's decision to vaccinate or not to vaccinate" [24], even somewhat more so than potential individual benefits of vaccination [44]. (We can also talk here of ''the self-and other-directed effects of vaccination" [45]).…”
Section: Responsibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Senior paediatricians in the UK have argued against mandatory vaccination as damaging trust in health systems and professionals, 8,9 while ethical discussions in Norway regretted the lack of debate on compulsion but reached a different conclusion. 10 This suggests instead the need for a more focused and innovative vaccination policy approach, combining rediscovery of past good practice and better application of new innovation, and their integration into a set of practical policies focussed on delivery. This paper reviews 10 aspects in order to indicate a suite of practical actions to complement and facilitate for children's vaccination the high-level Actions proposed by the Vaccination Summit.…”
Section: Rigbymentioning
confidence: 99%